Lagu Anak-Anak Berpengaruh Terhadap Kecerdasan Linguistik Anak Paud Kelompok B - WAHID ADI NUGRAHA, YUSUF; , Drs. Ilham Sunaryo, M.Pd. AUD (2016)
The purpose of this study was to determine the effect of children's songs to the linguistic intelligence group B of children in early childhood Islam Harapan 1 Gumpang Pabelan Kartasura in academic year 2015/2016. Method in this research is a quantitative method using a kind of experimental research with pre-experimental design research design. Pre-experimental research design using one group pretest-posttest design. This research was conducted in early childhood Islam Hope 1 Gumpang Pabelan Kartasura. Subjects in this study were children in group B in ECD Islam Hope 1 Gumpang Pabelan Kartasura with the number of 16 children. Data collection techniques in this research was conducted through observation, that observation participate (participan observation). Data analysis techniques in this study using ttest with SPSS 16.0 for Windows. The results of data analysis using t test obtained thitung -25 142 ≤ - ttabel -2.131 H0 rejected and Ha accepted which means there is the influence of children's songs on linguistic intelligence of children.